Communist Anxiety and the Liberal Defanging of Islam: De-Islamizing Muslim Consciousness - Muhammed Shamin P.P (LECTURES: Journal of Islamic and Education Studies, 2026)
Notwithstanding the diverse cultural and historical trajectories of modern societies, contemporary debates on religion and modernity frequently operate on the assumption that religious fervor must be restrained in order to achieve social progress and adapt to the changing demands of modern life. Although this assumption is commonly associated with Western liberalism, it is equally visible within the neo-colonial dynamics of postcolonial Kerala’s communist–secular project[1]. Kerala, widely celebrated for its religious pluralism, high literacy, and cultural diversity, has in recent years become the subject of growing criticism from religious and cultural practitioners and leaders. Within the broader context of neoliberal and neo-colonial transformation, neo-Marxist forces have played a leading role in advancing what critics describe as dialectical reinforcements that erode religious and cultural identities, particularly those of Muslim communities. These ideological pressures have increasingly generated anxiety and discouragement among religious populations regarding the future of cultural and religious pluralism, as modernity and liberalism advance their marginalizing tendencies[2]. The contemporary neo-Marxist influence in Kerala thus appears to reproduce patterns of cultural suppression reminiscent of colonial regimes. Drawing on theories of cultural alienation, ideological state apparatuses[3], and postcolonial critique, this article demonstrates how Kerala’s Marxist secularism operates within a distinct postcolonial and communist context while simultaneously mirroring this ideological formation’s objective of defanging Islam.